PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PT. BANK TABUNGAN NEGARA (BTN) KANTOR CABANG BANDAR LAMPUNG - Mulyadinata, Andi (Jurnal Bisnis Darmajaya, 2015)
Bank represent industrial company of service of because its product only give service activities to society, others also the bank represent service industries which its operational activity buy or sell banking service. In the world of banking specially the bank, owning good reputation or image represent very important factor because good image will give assorted of benefit. Putative bank will push client to use product in this case the service which there have in the bank. Writer limit research only at quality factor of service to Loyalitas of Cutomer PT. Savings Bank State (BTN) of Office Of Branch of Port Float. This Research aim to to know the level of influence of Quality of Service to Loyalitas of Cutomer of at PT. Savings Bank State ( BTN) of Office Of Branch of Port Float. Result of solution of influence of Quality of service to loyalitas of client PT. Savings Bank of State Branch Port Float obtained by Variable of service of t count (5446) > t of is tables of (1,75), its meaning is Ho refused and Is ha accepted, its conclusion there are influence of between service to loyalitas of client PT. Savings Bank of State Branch Port Float. Influence Or regresi of between quality of service to loyalitas of client PT. Savings Bank of State Branch Port Float equal to 0,806, while pursuant to value of R Square (R2) of equal to 0,650 that statistically the level of influence of quality of service to loyalitas give contribution of equal to 65%. While other 35% influenced by other;dissimilar factor is which is not checked in this research. Keyword : Service Quality, Loyalitas Customer